2021
DOI: 10.1007/s12274-021-3827-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of Fe-N-C electrocatalysts for oxygen reduction reaction: From nanoparticles to single atoms

Abstract: As an alternative energy, hydrogen can be converted into electrical energy via direct electrochemical conversion in fuel cells. One important drawback of full cells is the sluggish oxygen reduction reaction (ORR) promoted by the high-loading of platinumgroup-metal (PGM) electrocatalysts. Fe-N-C family has been received extensive attention because of its low cost, long service life and high oxygen reduction reaction activity in recent years. In order to further enhance the ORR activity, the synthesis method, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 227 publications
(250 reference statements)
0
27
0
Order By: Relevance
“…29,30 In recent years, many catalysts with M-N 4 active sites in a symmetric coordination environment have been reported. [31][32][33][34] However, with the deepening of the research, researchers found that compared with the relatively traditional M-N 4 symmetric structure, the coordination environment and electronic structure of the catalyst can be exibly designed through a reasonable adjustment of the asymmetric coordination structure. Asymmetric coordination approach brings satisfactory catalytic performance to M-N-C catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 In recent years, many catalysts with M-N 4 active sites in a symmetric coordination environment have been reported. [31][32][33][34] However, with the deepening of the research, researchers found that compared with the relatively traditional M-N 4 symmetric structure, the coordination environment and electronic structure of the catalyst can be exibly designed through a reasonable adjustment of the asymmetric coordination structure. Asymmetric coordination approach brings satisfactory catalytic performance to M-N-C catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Expressly, transition metal (i.e., M = Fe, Co, Ni, Cu, and Mn, etc.) and nitrogen dual doped carbon catalysts (i.e., M-N-Cs, containing relevant single-atom catalysts (SACs)) [40][41][42] have stood out among these candidates, owing to their beginning-of-life ORR activities approaching those of Pt-based catalysts in both acidic and alkaline electrolyte liquors [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal single atoms and nanoparticles are both promising candidates to replace state-of-the-art Pt-based ORR catalysts. Co and/or Fe-based compounds (metal/alloys, oxides, nitrides, sulfides, borides, and so on) are the most studied non-noble metal-based oxygen catalysts. To hinder the agglomeration of nanoparticles, they are usually supported on carbon substrates including carbon nanofibers, hierarchical nanoporous carbon, and carbon/graphene aerogels. , Though the supporting carbons increase the accessibility of the surface area and are capable of tuning the electronic structures, the hybrids still suffer from either poor intrinsic activity or unsatisfactory durability. Few-layer N-doped carbon encapsulation of nanoparticles could improve the stability but is usually detrimental to catalytic activities. Apart from nanoparticles, single-atom catalysts (SACs) of transition metals are an emerging candidate, having the merits of tunable electronic structures and exceptional atomic economy. Unfortunately, they are prone to a two-electron process. , The strong synergistic effect suggested in the hybrids of SACs and nanoparticles appears to overcome the deficiencies, leading to a four-electron reduction from O 2 to H 2 O at high efficiencies and favorable durability. This stimulates much current interest to develop hybrid catalysts made of SACs and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%